Kekeluargaan dan perkahwinan Melayu : konsep asas - Yaacob Harun; Universiti Malaya. Akademi Pengajian Melayu (Kuala Lumpur : Akademi Pengajian Melayu, Universiti Malaya, 1995)
Marriage and kinship of Malay ethnic group.
Includes bibliographical references (p. 141-142) and index.
Mode of access: Internet.
In Malay.
Keywords: Kinship -- Southeast Asia; Marriage -- Southeast Asia; Malays (Asian people)